Manipulative Effect of Environmental Conditions on the Growth and Yield of Cucumber Nourished with Poultry Manure in Sandy Loam Soil - Ali, Christian Chinedu; Asogwa, Vincent Chidindu; Izuakor, Chiamaka Francisca (Current Research in Agricultural Sciences, 2022)
There is high demand for cucumber because of its nutritional and medicinal implications. Despite the several benefits of the crop, there is little information on the agronomic performance of the crop in open and shaded conditions using different rates of poultry manure in south east Nigeria. The experiment was carried out to determine the effect of different rates of poultry manure on the growth and yield of cucumber in open and shaded conditions. This research was conducted in the research farm of the Agricultural Education Department, University of Nigeria, Nsukka. The experiment was laid out using RCBD (Randomized Complete Block Design) and replicated three times for both the open and shaded conditions. The poultry manure treatments applied were 0, 2 and 4ton/ha and data for the growth parameters were recorded on the 4th, 6th and 8th weeks after planting (WAP) while data on yield parameters were taken at harvest. The results indicated that cucumber planted under open system had the highest number of leaves, branches, stem girth, number of flowers, number of fruits and weight of fruits per plant when treated with 2ton/ha of poultry manure in comparison with 0ton/ha and 4ton/ha treatments under shaded system. The researchers therefore concluded that farmers in the study area can grow cucumbers in an open field with 2ton/ha poultry manure for optimal growth and yield of the crop.